EVALUASI APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) - Atikah, Siti; Rakhmawati, Intan; Dwi Astuti, Baiq Rosyida; Nabila, D.Tialurra Della (Jurnal Aplikasi Akuntansi, 2021)
This study aims to evaluate Siskeudes V2.0. R.0.1., from the system and its output, which is also analyzed is related to the measurement of efficiency and effectiveness of the use of village funds. Data collection is done by evaluating the application system, and calculating the financial ratio of siskeudes application output, in villages in West Lombok Regency. In terms of system evaluation, as a connection effect between the planning and budgeting stages, implementation and administration, to financial reporting, traceability and connectivity Siskeudes V2.0 R.0.1. better than Siskeudes V1.0.R1.06. The existence of the Activity Package in budgeting and implementing expenditures also makes it easier for the village government to make village financial statements. From the point of view of the village government, the average person has been able to estimate the using of funds and allocation in the activities field. Thus, the ability of the village government in West Lombok Regency in estimating routine expenditures and village capital expenditures (harmony), which has an effect on the efficiency and effectiveness of village funds, has been good. As a suggestion, because there is no automatic measurement of financial efficiency and effectiveness in Siskeudes to measure the financial performance of village governments, researchers advised the Ministry of Finance and the Ministry of Home Affairs to draw up regulations for calculating village financial ratios, as well as integrate them in Siskeudes applications.